Analysis of The Impact of Online Learning During the Covid-19 Pandemic on Cognitive Students At SMP Negeri 3 Anggeraja Kabupaten Enrekang - Rasda Gustianto; Hafied Cangara; Asfah Rahman (JURNAL NALAR PENDIDIKAN, 2022)
The purpose of this study was to analyze the impact of online learning on students' cognitive aspects during the COVID-19 pandemic at SMP Negeri 3 Anggeraja, Kabupaten Enrekang. The research method used is quantitative with an explanatory survey method to determine students' perceptions and experiences during online learning. The research sample was 114 students of SMP Negeri 3 Anggeraja, Kabupaten Enrekang. who were selected using the Probability Sampling Method with the slovin formula, then this sample was taken using the proportional stratified sampling method. The research instrument used was a closed questionnaire with a modified Likert scale model interval measurement. The data that has been collected was then analyzed using simple linear regression analysis with the help of the SPSS Version 25 program for Windows 10. The results found that there was a significant influence between Online Learning on the cognitive aspects of students at SMP Negeri 3 Anggeraja, Kabupaten Enrekang. From the research results to the teacher aspect pay special attention to the cognitive development of students in online learning.